(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Heart valve disease is a major health concern, with existing treatment options—mechanical and bioprosthetic valves—presenting significant limitations such as thrombosis risks, anticoagulation requirements, and limited durability. Bioengineered heart valves offer a revolutionary alternative by integrating tissue engineering, regenerative medicine, and advanced biomaterials. This article explores innovations in bioengineered heart valves, their advantages, challenges, and future prospects in cardiovascular medicine.